ANTIMICROBIAL POTENTIALS OF SILVER COLLOIDAL (NANORODS) ON CLINICAL ISOLATES IN BAYELSA STATE, NIGERIA - Tatfeng, Mirabeau Y; Ojo, T O; Agwale, Simon M (African Journal of Traditional, Complementary and Alternative Medicines, 2012)
Antimicrobial resistance in developing countries has long been an issue of major concern. Nanotechnology has become an eye opener for the intervention on multiple drug resistance organisms. In this study we investigated the antimicrobial potentials of Silver Nitrate (nanorods) solution used in managing infectious diseases, the Minimum Inhibitory Concentration (MIC) and Minimum Bactericidal Concentration (MBC) of the product against microbial isolates were determined using standard microbiological techniques. The mean MIC and MBC of silver nitrate solution on fungi (0.16 μg/ml and 0.29 μg/ml respectively) was significantly lower than that of Gram positive organisms (2.35μg/ml and 2.62μg/ml) and Gram negative organisms (2.05 μg/ml and 2.10 μg/ml). Of all the Gram positive organisms, Staphylococcus spp recorded the lowest mean MICand MBC while in the Gram negative organisms group, E. coli isolates showed the lowest mean MIC and MBC of the silver nitrate solution, though not significantly different from the other isolates. In conclusion, results from this study revealed that Silver Nitrate(nanorods) may have be broad spectrum in activity, but with higher antifungal potentials.